“Keeping up with the Joneses.” A sociological content analysis of advertising catalogues with the eye-tracking method - Isański, Jakub; Leszkowicz, Mateusz (Qualitative Sociology Review, 2011)
Is it possible to look at something without actually noticing it? Is it possible to see something in the picture that is not really there? The answers to these philosophical questions can be obtained by comparing the results of eye-tracking tests combined with interviews based on sociological theories. The answers, however, have more than the philosophical dimension in that they can provide insight into everyday processes of social perception and its application, also for commercial purposes. In the design phase of the present study, we chose a popular advertising folder available for free for the average consumer. While showing the selected photographs to the respondents (all the pictures included people portrayed during everyday activities), we asked them to pay particular attention to the situations presented. Afterwards, each participant took part in a standardised interview. In our view, the conclusions formulated on the basis of the obtained results are relevant not only to the investigated catalogue, but can also be treated as an indicator of how people usually browse through advertisements and what kind of inferences they make about the world on that basis. While most attention should be given to watching the advertisements, we constitute our dreams of a perfect life, environment and the items that furnish it.